Pirates on the liquid shores of liberal democracy - Cammaerts, Bart (Javnost (Ljubljana), 2015)
In this article, the movement frames of European Pirate Parties are analysed through a thematic analysis of texts relating to the Pirate Parties and transcripts of semi-structured interviews with representatives of Pirate Parties across three European countries - Germany, the United Kingdom and Belgium. At the level of the diagnostic and prognostic frames the Pirate Parties address contentious issues and discourses about civic liberties, privacy and access to knowledge in a digital era, but they also critique liberal representative democracy as such, which they argue needs to incorporate delegative models of democracy. In addition to this, a pro-social frame is presented emphasising free education and a basic income. In order to achieve these aims the Pirate Parties develop a distinct collective identity and foster political agency through activism and by participating in electoral politics. Lack of electoral appeal and low levels of membership is some countries, inability to deal with conflicts and an unwillingness to clarify the ideological position and the precise relationship between a libertarian freedom-related agenda and a social justice agenda represent challenges for the Pirate Parties.
Keywords: Liberal democracy; Liberalna demokracija; piratske stranke; Political parties; Political programs; Politične stranke; Politični programi